2008
DOI: 10.1117/12.774576
|View full text |Cite
|
Sign up to set email alerts
|

Process flow innovations for photonic device integration in CMOS

Abstract: Multilevel thin film processing, global planarization and advanced photolithography enables the ability to integrate complimentary materials and process sequences required for high index contrast photonic components all within a single CMOS process flow. Developing high performance photonic components that can be integrated with electronic circuits at a high level of functionality in silicon CMOS is one of the basic objectives of the EPIC program sponsored by the Microsystems Technology Office (MTO) of DARPA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…Si nitride and Si oxi-nitride are transparent for wavelengths longer than 600 nm. [25][26][27] This is substantially lower than the absorption edge of Si, which lies at 1100 nm. If Si LEDs and Si p − n detectors are used, Si CMOS technology does not have to rely on III-V or Si-Ge technology.…”
Section: Optical Properties Of Cmos Integrated Circuitmentioning
confidence: 94%
See 1 more Smart Citation
“…Si nitride and Si oxi-nitride are transparent for wavelengths longer than 600 nm. [25][26][27] This is substantially lower than the absorption edge of Si, which lies at 1100 nm. If Si LEDs and Si p − n detectors are used, Si CMOS technology does not have to rely on III-V or Si-Ge technology.…”
Section: Optical Properties Of Cmos Integrated Circuitmentioning
confidence: 94%
“…23,24 Other transparent layers such as Si oxi-nitride and Si dioxide can be added as further overlayers. [25][26][27] The optical transparency of the different layers varies slightly. The dimensions and optical variables as associated with above 0.35 μm CMOS integrated circuit technology are presented in Table 1.…”
Section: Optical Properties Of Cmos Integrated Circuitmentioning
confidence: 99%
“…The inter-metallic oxide, positioned between metallic layers, are CVD plasma deposited and mainly used as electrical isolation between the metal layers. Literature surveys (Beals et al , 2008, Gorin et al, 2008 show that, even so, these layers are porous, they offer suitable propagation for the longer mid infra-red wavelengths, where structural defects, such as porosity, grain boundaries and side wall scattering due to roughness play a lesser role . The metallic layers bonding to the oxide inter-metallic oxide layers can be used as effective reflectors or optical confinement layers.…”
Section: Optical Compatibility Of Cmos Technologymentioning
confidence: 99%
“…Advances in electronic-photonic integration have enabled optical interconnect technologies with greater integration, smaller distances, and higher bandwidths [21], [22], [15], [28]. Further, recent research [19] has shown that optical devices can be built using standard CMOS processes, thereby allowing optics to replace global wires and on-chip buses [1].…”
Section: Optical Devices Backgroundmentioning
confidence: 99%